The Semantic redundancy in Old Church Slavonic - Zábranský, Lukáš (Bohemica Olomucensia, 2012)
In the study the author seeks to shed light on the issue of how to view words formed by composition in the Old Church Slavonic literature. The author focuses on the semantic redundancy in compounds, in which the reach of influence of Greek on the phenomenon of composition in Old Church Slavonic was observed.